CT cholangiography in dogs with gallbladder mucocoele. (30th March 2018) - Hayakawa, S.; Sato, K.; Sakai, M.; Kutara, K.; Asano, K.; Watari, T.
Abstract : Objectives: To summarise CT cholangiography findings in dogs with gallbladder mucocoele. Materials and Methods: Each of 10 dogs with gallbladder mucocoele underwent CT cholangiography using meglumine iotroxate before cholecystectomy. The following structures of the biliary system were evaluated: the right and left hepatic ducts, common hepatic duct, cystic duct, common bile duct and gallbladder. Results: The hepatic duct, cystic duct, common bile duct and gallbladder were imaged by contrast‐enhanced CT cholangiography. The passage of the contrast medium through the bile duct into the duodenum was visible in nine dogs. The curved planar reformation images of two dogs showed they had filling defects in the bile duct system. In one dog with hyperbilirubinaemia due to chronic hepatitis, the bile duct system was not completely contrast‐enhanced. Surgical exploration revealed no evidence of common bile duct obstruction in any dog. Clinical Significance: CT cholangiography delineates the structural characteristics of the biliary system and partially estimates its patency in dogs with gallbladder mucocoele. Therefore this procedure may be useful as a preoperative screen of the bile duct system in dogs with gallbladder mucocoele.